Surface acoustic wave resonators in the quantum regime - Manenti, R; Peterer, M; Nersisyan, A; Magnusson, E; Patterson, A; Leek, P (American Physical Society, 2016)
We present systematic measurements of the quality factors of surface acoustic wave (SAW) resonators on ST-X quartz in the gigahertz range at a temperature of 10mK. We demonstrate an internal quality factor Qi approaching 0.5 million at 0.5GHz and show that Qi≥4.0×104 is achievable up to 4.4GHz. We show evidence for a polynomial dependence of propagation loss on frequency, as well as a weak drive power dependence of Qi that saturates at low power, the latter being consistent with coupling to a bath of two-level systems. Our results indicate that SAW resonators are promising devices for integration with superconducting quantum circuits.